2020
DOI: 10.1111/apt.16100
|View full text |Cite
|
Sign up to set email alerts
|

Digital pathology: accurate technique for quantitative assessment of histological features in metabolic‐associated fatty liver disease

Abstract: Summary Background Histological evaluation of metabolic‐associated fatty liver disease (MAFLD) biopsies is subjective, descriptive and with interobserver variability. Aims To examine the relationship between different histological features (fibrosis, steatosis, inflammation and iron) measured with automated whole‐slide quantitative digital pathology and corresponding semiquantitative scoring systems, and the distribution of digital pathology measurements across Fatty Liver Inhibition of Progression (FLIP) algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 65 publications
0
21
0
4
Order By: Relevance
“…The study protocol conformed to the ethical guidelines of the 1975 Declaration of Helsinki and received ethical approval by the Institution Review Board of the three participating hospitals (2016/209; 2017/0031/PI, and 29/2019). A portion of the included participant data ( n = 78) has already been published regarding technical developments of digital pathology [ 17 ]. The prior study used a simpler methodology for digital image analysis and did not evaluate other chronic hepatitis etiologies beyond NAFLD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study protocol conformed to the ethical guidelines of the 1975 Declaration of Helsinki and received ethical approval by the Institution Review Board of the three participating hospitals (2016/209; 2017/0031/PI, and 29/2019). A portion of the included participant data ( n = 78) has already been published regarding technical developments of digital pathology [ 17 ]. The prior study used a simpler methodology for digital image analysis and did not evaluate other chronic hepatitis etiologies beyond NAFLD.…”
Section: Methodsmentioning
confidence: 99%
“…The histopathological features of participants are summarized in Table 2. Median biopsy length was 20 (17)(18)(19)(20)(21)(22)(23) mm and included 10 (8-13) portal tracts. Histological review showed that 23% had mild steatosis (S1, n = 36), 22% had moderate steatosis (S2, n = 34), and 22% presented severe steatosis (S3, n = 35).…”
Section: Patients and Histological Characteristicsmentioning
confidence: 99%
“… 76 Indeed, digital pathology is likely to dramatically enhance the value of the liver biopsy in the coming years. 77 , 78 …”
Section: Current and Future Roles Of Liver Histologymentioning
confidence: 99%
“…76 Indeed, digital pathology is likely to dramatically enhance the value of the liver biopsy in the coming years. 77,78 Recent advances in slide scanners now allow the creation of "digital/virtual" slides that allow whole slide imaging (WSI) and additional techniques, such as combining multiphoton microscopy (MPM) with advanced clearing and fluorescent stains (Clearing Histology with MultiPhoton Microscopy (CHiMP)) or use of matrix assisted laser desorption/ionization (MALDI) mass spectrometry. 79 The combination of expert evaluation, digital pathology and artificial intelligence is likely to further enhance the value of histopathology.…”
Section: Researchmentioning
confidence: 99%
“…Algorithms in arti cial intelligence (AI) may resolve issues with interrater variability [54], measurement uncertainty and error by providing quantitative assessments of tissue histology and other tangential tasks which may be of immediate value [55,12,56,57,58,59]. A combination of both rater uncertainty and incomplete information about the histology may present additional challenges for training and evaluating AI technologies.…”
Section: Opportunitiesmentioning
confidence: 99%